(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to compare the effectiveness of double-leg hurdle jumps and single-leg hurdle jump training in increasing the shooting speed of football players at SMPN 3 Bontomarannu. This research method uses an experimental design with a paired sample t-test to analyze the differences in the results of the two training methods. The research sample consisted of 22 players divided into two groups, each doing double leg hurdle jumps training as many as 11 players and single leg hurdle jumps also 11 players for 16 meetings. The results of the study showed that double leg hurdle jumps training produced a mean value of 0.04818 with a significance of 0.000 (p <0.05), indicating a more substantial increase compared to single leg hurdle jumps which had a mean value of 0.0163 and a significance of 0.015 (p <0.05). These findings indicate that double-leg hurdle jump training is more effective in increasing shooting speed. This study concludes that double-leg hurdle jump training has a more significant effect on the shooting speed of football players than single-leg hurdle jumps.